Corn productivity in function of surface application of lime in differents management systems and cultural preparation - Narimatsu, Karem C. P.; Mello, Luiz M. M. De [UNESP]; Domingues, Luis A. Da Silva; Chioderoli, Carlos A.; Lima, Ronaldo C. [UNESP] (Associação Brasileira de Engenharia Agrícola (SBEA), 2014)
The evaluation of technologies employed at the agricultural production system such as crop rotation and soil preparation, both associated with crop-livestock integration, is crucial. Therefore, the aim of the present study was to evaluate the incorporation of lime for three no-tillage systems and cultural managements in system of crop-livestock integration, with emphasis on corn grain yield. The experiment was conducted from January 2003 to April 2005 at Selvíria city, MS, in Dystroferric Red Latosol, clay texture. The experimental design was randomized blocks with split plots consisted of three main treatments, aimed the soil physics conditioning and the incorporation of lime: PD - No-no-tillage; CM - minimum no-tillage, and PC - conventional no-tillage; and of two secondary treatments related to the management: rotation and crop succession, with four replications. Data on agronomic traits of maize were analyzed: plant height, stem diameter, height of the first spike insertion, 100 grains weight and grain yield. The results showed that the maize produced under the system of crop-livestock integration is quite feasible, showing that grain yields are comparable to averages in the region and the different soil physical conditioning and incorporation of lime did not influence the corn yield as well as the cultural managements, rotation and succession, did not affect the maize crop behavior after two years of cultivation.

A avaliação das tecnologias empregadas ao sistema de produção agrícola, tais como rotação de culturas e preparo de solo, ambos associados à integração lavoura-pecuária, é importante para tomadas de decisões futuras. Portanto, objetivou-se, no presente trabalho, avaliar a incorporação de calcário por três sistemas de preparo do solo e dois manejos culturais, em sistema de integração lavoura-pecuária, com ênfase para produtividade de grãos de milho. O experimento foi conduzido no período compreendido de janeiro de 2003 a abril de 2005, no município de Selvíria-MS, em Latossolo Vermelho distroférrico, textura argilosa. O delineamento experimental adotado foi o de blocos ao acaso, com parcelas subdivididas, constituídas por três tratamentos principais, visando o condicionamento físico do solo e a incorporação de calcário: PD - Plantio Direto; CM - Cultivo Mínimo, e PC - Preparo Convencional; e por dois tratamentos secundários, relacionados ao manejo: rotação e sucessão de culturas, com quatro repetições. As características agronômicas do milho analisadas foram: altura de planta, diâmetro de colmo, altura de inserção da primeira espiga, massa de 100 grãos e produtividade de grãos. Os resultados mostraram que não houve diferenças estatísticas na produtividade do milho, tanto em função dos tratamentos de manejo do solo para incorporação de calcário, como nos manejos culturais, rotação e sucessão, após dois anos de cultivo.
Produtividade de milho em função da aplicação superficial de calcário em diferentes sistemas de preparo e manejo cultural
Keywords: sistema plantio direto; cultivo mínimo; preparo convencional; integração lavoura-pecuária; rotação de culturas; no tillage system; minimum tillage; conventional tillage; crop-livestock integration; crop rotation